Investigation of Middle School Students' Model of Astronomy Events and Information Sources of Incorrect Model - Tufan Inaltekin; Uğur Akbaba (International Journal of Contemporary Educational Research)
The purpose of this study is to reveal middle school students' model understanding and information sources of incorrect model related to basic astronomy topics included in the Turkish middle school science curriculum. The study is a descriptive study focusing on qualitative data. The sample of the study includes 197 students (aged 12-13) attending eighth grade in seven schools in a city in northeastern Türkiye. Data for the study was collected using the "Astronomy Models and Source Information Form." In this study, descriptive analysis was used as one of the qualitative data analysis methods. Findings indicate that the majority of students possess the incorrect model understanding concerning subjects such as "Solar Eclipse," "Lunar Eclipse," "The Phases of the Moon," "Formation of Seasons," and "Formation of Night and Day," which are part of the middle school science curriculum. The findings also show that teachers and textbooks came to the fore as sources of information in the incorrect model.